2018
DOI: 10.3989/gya.0666171
|View full text |Cite
|
Sign up to set email alerts
|

Frying performance of two virgin oils from <em>Cornicabra</em> olives with different ripeness indices

Abstract: The frying performance of two virgin olive oils (VOO) from Cornicabra olives of different ripeness indices, 2.08 for VOO1 and 4.13 for VOO2, was evaluated. Thermal, oxidative and hydrolytic alterations were determined throughout 40 frying operations with potatoes. The initial oils showed similar fatty acid compositions and oxidative stability indices as determined by Rancimat, but VOO1 presented higher amounts of total polyphenols and tocopherols. The oils showed high and similar frying performance. No signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…In agreement with other studies, no significant differences were found for the hydrolysis compounds, i.e. DG and FFA, as a consequence of frying (Sebedio et al, 1996;Olivero-David et al, 2017). Given that the levels of hydrolysis products were high in the fresh oil, the limit of 25% TPC was reached when the thermal and oxidative degradations were not elevated compared to refined oils obtained from oleaginous seeds.…”
Section: Physicochemical Changes Of the Oil During Deep-fryingsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with other studies, no significant differences were found for the hydrolysis compounds, i.e. DG and FFA, as a consequence of frying (Sebedio et al, 1996;Olivero-David et al, 2017). Given that the levels of hydrolysis products were high in the fresh oil, the limit of 25% TPC was reached when the thermal and oxidative degradations were not elevated compared to refined oils obtained from oleaginous seeds.…”
Section: Physicochemical Changes Of the Oil During Deep-fryingsupporting
confidence: 91%
“…The TPC content increased linearly with the frying time (R 2 = 0.96), as observed in numerous frying studies (Olivero-David et al, 2017). However, no significant increment was found from the first to the second day of frying, i.e.…”
Section: Physicochemical Changes Of the Oil During Deep-fryingsupporting
confidence: 66%
“…Virgin olive oils are highly resistant to alteration during frying mainly because of their high monounsaturated-to-polyunsaturated fatty acid ratio and the antioxidant activity of phenolic compounds [ 43 ]. However, frying behavior of virgin olive oils depends considerably on the olive variety [ 44 ] and olive ripening degree [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acid (FA) composition and the presence of antioxidants are the two main factors influencing the stability of the oil against chemical reactions during a deep‐fat frying process (Yu et al., 2018). Oils with high levels of saturated FA (SFA) are very stable but they are not nutritionally preferred (Olivero‐David et al., 2018). According to the Iranian National Standards Organization, the SFA content should be <30% in the frying oils (INSO, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Iranian National Standards Organization, the SFA content should be <30% in the frying oils (INSO, 2023). Oils rich in polyunsaturated FA (PUFA) are highly unstable at elevated temperatures (Olivero‐David et al., 2018). For example, oils with higher linolenic acid can decompose after exposure to heat and air (Mao et al., 2020).…”
Section: Introductionmentioning
confidence: 99%